Validation of ecotoxicological methods for wastewater monitoring to be discharged to marine-coastal and transitional environments - Advanced technologies for wastewater treatment (SBR and MBR) as case studies - LIBRALATO, Giovanni (2007)
Transitional and marine coastal discharges are gaining more attention due to the increase of human pressures on coastal areas. The proposal for wastewater biomonitoring via brackish and salt water toxicity testing organisms on an end-of-pipe basis can provide information about wastewater treatment plants management, wastewater treatment technologies efficiency in toxicity reduction/removal and final discharge potential hazard. Activated sludge sequencing batch reactor, ultra-filtration membrane biological reactors, activated carbon and reverse osmosis were checked in small and medium sized configurations for their discharge quality. Domestic/hotel, mixed domestic, septic tank and industrial (glass factory), TNT, table olive brine and aircraft washing wastewaters were assessed before and after their relative treatment process via Artemia franciscana, Vibrio fischeri, Crassostrea gigas and Mytilus galloprovincialis toxicity tests. All the main physico-chemical parameters were also provided. The ultra-filtration membrane biological reactors showed to improve more efficiently the quality of the discharge from both the physico-chemical and the ecotoxicological point of view, suggesting more support by regulatory authorities on their implementation. Moreover, it was evidenced that A. franciscana is not suitable for wastewater toxicity testing, whereas all other bioassays are relatively sensitive and reliable.